Diagnostic Accuracy of Ultrasound in Detecting Choledocholithiasis in Patients with Obstructive Jaundice: A Comparative Study with MRCP as Gold Standard - Amina Hameed, Zainab Zahid, Khadija Nasir, Zahid Saeed, Jahangir, Irshad Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the diagnostic accuracy of ultrasound (US) in detecting choledocholithiasis in patients with obstructive jaundice, comparing it with Magnetic Resonance Cholangiopancreatography (MRCP) as the gold standard. Methods: A prospective study was conducted on 130 patients with suspected obstructive jaundice from January 2023 to June 2023. All patients underwent ultrasound and MRCP. The diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of US were determined. Results: The sensitivity of US was found to be 65%, specificity 92%, PPV 84%, and NPV 80%. MRCP showed higher sensitivity (91%) and specificity (96%) in detecting choledocholithiasis. Conclusion: Ultrasound is a useful screening tool for choledocholithiasis but has limitations in sensitivity compared to MRCP. Its high specificity suggests it remains valuable in confirming the absence of the disease, while MRCP is preferred for definitive diagnosis. Keywords: Ultrasound, Choledocholithiasis, Obstructive Jaundice, Magnetic Resonance Cholangiopancreatography, Diagnostic Accuracy, Sensitivity, Specificity